eRASSt J040515.6 − 745202, an X-ray burster in the Magellanic Bridge - Haberl, F.; Vasilopoulos, G.; Maitra, C.; Valdes, F.; Lang, D.; Doroshenko, V.; Ducci, L.; Kreykenbohm, I.; Rau, A.; Weber, P.; Wilms, J.; Maggi, P.; et al. (Astronomy and Astrophysics, 2023)
Context. During the third all-sky survey (eRASS3), eROSITA, the soft X-ray instrument aboard Spectrum-Roentgen-Gamma, detected a new hard X-ray transient, eRASSt J040515.6 − 745202, in the direction of the Magellanic Bridge. Aims: We arranged follow-up observations and searched for archival data to reveal the nature of the transient. Methods: Using X-ray observations with XMM-Newton, NICER, and Swift, we investigated the temporal and spectral behaviour of the source for over about 10 days. Results: The X-ray light curve obtained from the XMM-Newton observation with an ∼28 ks exposure revealed a type-I X-ray burst with a peak bolometric luminosity of at least 1.4 × 1037 erg s−1. The burst energetics are consistent with a location of the burster at the distance of the Magellanic Bridge. The relatively long exponential decay time of the burst of ∼70 s indicates that it ignited in a H-rich environment. The non-detection of the source during the other eROSITA surveys, twelve and six months before and six months after eRASS3, suggests that the burst was discovered during a moderate outburst which reached 2.6 × 1036 erg s−1 in persistent emission. During the NICER observations, the source showed alternating flux states with the high level at a similar brightness as during the XMM-Newton observation. This behaviour is likely caused by dips as also seen during the last hour of the XMM-Newton observation. Evidence for a recurrence of the dips with a period of ∼21.8 h suggests eRASSt J040515.6 − 745202 is a low-mass X-ray binary (LMXB) system with an accretion disk seen nearly edge on. We identify a multi-wavelength counterpart to the X-ray source in UVW1 and g, r, i, and z images obtained by the optical/UV monitor on XMM-Newton and the Dark Energy Camera at the Cerro Tololo Inter-American Observatory. The spectral energy distribution is consistent with radiation from an accretion disk which dominates the UV and from a cool late-type star detected in the optical to infrared wavelengths. Conclusions: After the discovery of X-ray bursts in M 31, the Magellanic Bridge is only the second location outside of the Milky Way where an X-ray burster was found. The burst uniquely identifies eRASSt J040515.6 − 745202 as an LMXB system with a neutron star. Its location in the Magellanic Bridge confirms the existence of an older stellar population which is expected if the bridge was formed by tidal interactions between the Magellanic Clouds, which stripped gas and stars from the clouds.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Magellanic Clouds; stars: mass-loss; stars: neutron; X-rays: binaries; X-rays: bursts; X-rays: individuals: eRASSt J040515.6-745202